What determines BITs? - Jeffrey H. Bergstrand; Peter Egger (Center for Economic Studies and ifo Institute (CESifo), 2011)
Bilateral investment treaties (BITs) have proliferated over the past 50 years such that the number of pairs of countries with BITs is roughly as large as the number of country-pairs that belong to bilateral or regional preferential trade agreements (PTAs). The purpose of this study is to provide the first systematic empirical analysis of the economic determinants of BITs and of the likelihood of BITs between pairs of countries using a qualitative choice model, and in a manner consistent with explaining PTAs. We develop the econometric specification for explaining the two based upon a general equilibrium model of world trade and foreign direct investment with three factors, two products, and explicit natural as well as policy trade and investment costs among multiple countries in the presence of national and multinational firms. The empirical model for BITs and PTAs is bivariate in nature and supports a set of hypotheses drawn from the general equilibrium model. Using the preferred empirical model, we correctly predict approximately 85 (75) percent of all BITs (PTAs) correctly, relative to an unconditional probability of only 11 (16) percent.
Keywords: F10; F20; 330; bilateral investment treaties; foreign direct investment; multinational firms; free trade agreements; international trade; Investitionsgarantie; Internationale Wirtschaftsbeziehungen; Freihandelszone; Direktinvestition; Multinationales Unternehmen; Allgemeines Gleichgewicht; Schätzung; Welt